Cardiac Involvement in Dermatomyositis: Successful Management using a Novel IVIg Preparation - Waigand, Simon; Winkler, Julia K; Enk, Alexander H (Archives of Clinical and Medical Case Reports, 2025)
Dermatomyositis (DM) is a rare idiopathic inflammatory myopathy characterized by skin, muscle and various systemic involvement, with cardiac manifestations serving as critical prognostic factors. The management of cardiac involvement in DM remains challenging and subject to ongoing debate. We present a 72-year-old female with DM complicated by cardiac involvement, refractory to corticosteroids and mycophenolate mofetil. Treatment with a novel intravenous immunoglobulin preparation led to a marked reduction in cardiac enzyme levels, as well as improvements in strength, dyspnea, and dysphagia. This IVIg preparation differs regarding manufacturing process and shows a favorable safety profile. This case highlights the potential of IVIg in managing cardiac involvement in DM.